2022
DOI: 10.1136/bjophthalmol-2021-319809
|View full text |Cite
|
Sign up to set email alerts
|

Application of mydriasis and eye steering in ultrawide field imaging for detecting peripheral retinal lesions in myopic patients

Abstract: PurposeTo compare mydriatic and eye-steering ultrawide field imaging (UWFI) with standard non-mydriatic UWFI examination in detecting peripheral retinal lesions in myopic patients.MethodsCross-sectional, observational study. 220 eyes of 110 myopic patients with known peripheral retinal lesions in at least one eye under Goldmann three mirror contact lens examination were recruited. Non-mydriatic standard and eye-steering UWFI images were taken centrally and with eye-steering technique in upper, lower, nasal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Previously, the effect of AL on detecting retinal tears remained controversial. 11,20,28,29 In our study, B-scan US performed well in highly myopic subgroup perhaps because of the higher rate of horseshoe tears (40%) in this AL subgroup, whereas UWFI performed better than B-scan US in extreme myopic subgroup, probably because extreme long eyes have more complicated abnormalities of vitreoretinal interface, 30 thus interfering with the observation of retinal tears by B-scan US. The good performance of UWFI in extreme long eyes may be also related to the higher percentage of atrophic holes (50%), which are more easily detected by UWFI in this group.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Previously, the effect of AL on detecting retinal tears remained controversial. 11,20,28,29 In our study, B-scan US performed well in highly myopic subgroup perhaps because of the higher rate of horseshoe tears (40%) in this AL subgroup, whereas UWFI performed better than B-scan US in extreme myopic subgroup, probably because extreme long eyes have more complicated abnormalities of vitreoretinal interface, 30 thus interfering with the observation of retinal tears by B-scan US. The good performance of UWFI in extreme long eyes may be also related to the higher percentage of atrophic holes (50%), which are more easily detected by UWFI in this group.…”
Section: Discussionmentioning
confidence: 50%
“…Unlike the B-scan US, UWFI directly provides a retinogram of more than 80% of the retinal surface and relies little on the proficiency of technicians, acting as a reliable diagnostic method for various kinds of retinopathy. 17,18 It can achieve the sensitivity up to 86.5% to 89.2% for retinal lesions among noncataractous eyes, 11,19 expected to be a convenient tool for fast screening. In cataractous eyes, UWFI tends to show better penetrability than indirect ophthalmoscopy according to the clinical experience from doctors, although poor media transparency may affect image resolution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of ultrawide field imaging preoperatively may be helpful to detect peripheral retinal lesions. A study by Li et al [11 ] has demonstrated that the sensitivity of mydriatic eye steering ultrawide field imaging for detecting peripheral retinal lesions in myopic eyes was 86.52% compared with 41.48% with nonmydriatic standard imaging. There is no consensus whether prophylactic laser photocoagulation should be performed for asymptomatic retinal lesions prior to surgery [12].…”
Section: Preoperative Considerationsmentioning
confidence: 99%